THE DEVELOPMENT OF THE NATIONAL SYSTEM OF EDUCATION AND UPBRINGING IS THE BASIS FOR CREATING THE FOUNDATION OF THE THIRD RENAISSANCE (British Journal of Global Ecology and Sustainable Development, 2022)
The article examines the policy implemented in Uzbekistan for the development of the national system of education and upbringing in the conditions of the formation of the foundations of the third Renaissance and the attitude of society to the personality of the teacher and the opportunities created by the conditions for young people. In the development of developed societies, along with the economic sphere, science, innovation, education, health and sports, culture and art are put on the front lines, and this is not in vain. Already, the lesson of history has always been philosophically justified, showing people what exactly needs to be changed.